2014
DOI: 10.1111/nbu.12118
|View full text |Cite
|
Sign up to set email alerts
|

Infant nutrition – diet between 6 and 24 months, implications for paediatric growth, overweight and obesity

Abstract: Infants are growing rapidly from 6-24 months and have high nutrient needs in proportion to their body size. This sub-group of the population are prone to dietary imbalances and inadequacies. It is of vital importance to get nutrition right during this time period to support appropriate growth and development.Overweight and obesity rates are increasing in pre-school children, and maternal nutritional status and early life feeding have been identified as 'critical windows' for obesity risk. After the recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Therefore, it is important for parents to select breakfast and snack options that are nutritionally adequate for the infant's diet and to not exceed recommendations when added to the infant's diet. More attention needs to be focused upon infant snacks as national surveys have shown that snacking increases with age and that a higher percentage of 12‐ to 18‐month‐olds snack on ‘sugar preserves and confectionary’ (63%) compared with ‘savory snacks’ (43%), and there is currently limited data available in relation to their nutritional suitability (Hardwick & Sidnell, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important for parents to select breakfast and snack options that are nutritionally adequate for the infant's diet and to not exceed recommendations when added to the infant's diet. More attention needs to be focused upon infant snacks as national surveys have shown that snacking increases with age and that a higher percentage of 12‐ to 18‐month‐olds snack on ‘sugar preserves and confectionary’ (63%) compared with ‘savory snacks’ (43%), and there is currently limited data available in relation to their nutritional suitability (Hardwick & Sidnell, ).…”
Section: Resultsmentioning
confidence: 99%
“…Breastfeeding may confer protective effects against obesity (discussed by Hardwick & Sidnell 2014) through a number of different mechanisms, including self-regulation of energy intake and appetite entrainment. Breastfeeding also promotes acceptance of new foods such as vegetables (discussed by Venter & Harris 2009).…”
mentioning
confidence: 99%
“…Most complementary foods used in low-income households are starchy porridges traditionally prepared from locally available cereals (Abeshu, Lelisa, & Geleta, 2016). Such complementary foods are often characterized by low nutrient densities, poor protein quality, high bulk, low mineral bioavailability and low energy (Hardwick & Sidnell, 2014). This contributes to the high prevalence of under nutrition among children, especially in developing countries (Abeshu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of poor nutrition on growth and development are very pronounced at this stage, as breast milk alone becomes inadequate to meet the nutritional requirements of infants as from six months (Hardwick & Sidnell, 2014;World Health Organization, 2001). Nutritional deficits acquired during this period are difficult to compensate for later in childhood (World Health Organization, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation